Green salvation the adaptive reuse of the Veterans Memorial Medical Center and golf course as an evacuaion center - Silvestre, Sophia Regina P.
In recent years, talk of the "Big One" has been circling around the Greater Metro Manila Area; this is a projected 7.2 magnitude earthquake that may be generated by the movement of the 100-kilometer long West Valley Fault. The Philippine Institute of Volcanology and Seismology along with the Department of Science and Technology have discovered in recent studies that this event may occur within this lifetime. An evacuation plan drawn up in 2013 by the Metro Manila Development Authority designated the use of public open spaces as evacuation centers in times of disaster; these last remaining open areas within the city were identified as parks or gold courses. This study aims to create a prototype design that will enable golf courses located within high-density urbanscapes to become evacuation centers in the event of an intense natural calamity; in this case, the "Big One". Looking at a dense urban sprawl that is less than 5 kilometers away from the West Valley Fault, one can only wish for the best that this dissertation may lessen the casualties and hardships that may come sooner rather than later. Armed with the data, research, and proposed solutions in this book, the researcher hopes to refine the emergency evacuation plan proposed by the MMDA.